Representações sociais da ciência e dos cientistas em roteiros de peças de teatro - Ginebro, Tiago Nadim (Universidade Federal de São Carlos, 2015)
This dissertation aims to analyze what are the social representations about the science and be a scientist present in two scripts of plays of São Carlos groups of theatre. Such social representations are not reproductions of surrounding the authors of the scripts. Cultural values are assimilated through a network built collectively from pre-existing knowledge that allow such individuals to experience a social practice. Justified to serve the collectives that develop a university extension work, especially in basic education. Contributes to the praxis of artists and writers with regard to reflect in his plays, his debates with the public after shows or even on how they look. The survey featured a documentary analysis, scripts, using content analysis as methodological procedure. Created two categories of analysis: social representations of science in both scripts. Divide into three subcategories: "science as absolute truth (sure) and/or transience (doubt)"; "the scientific field and the search for recognition"; and "the relationship between science and fantasy". And the second category, the social representations of the scientist in the two scripts of theater. We conclude that the word "truth", its synonyms or antonyms may not have a large occurrence in both scripts, however that doesn't stop to observe a social representation of science that is sometimes taken as absolute. There is also in its Constitution space for doubt, uncertainty, but accompanied by a sense of hierarchy. The success of an experiment, the formulation of a model or a production technology by any one of the characters leads to elevation of this to a prominent post inside the camp. Is a young scientist trying to impress your tutor or a renowned researcher trying to stand out in relation to their peers, the legitimacy on this is a goal, sometimes hidden, in both scripts. For their motivations, the authors build characters that act in order to generate id us bystanders and, for that, use their social representations. They have elements in common with the representations that the public has. One is that the scientist is differentiated from other people. Even without any mannerisms, the characters end up moving away, even though geographically in an isolated house.
Keywords: Educação; Representações sociais; Teatro; Ciência; Cientistas; Social representations; Scientific Theatre; Sciences; Scientists; CIENCIAS HUMANAS::EDUCACAO